The Examination of the 4th Graders’ Reading Comprehension Skills in Terms of the Sentiments Given in Reading Texts - Esra Çetin; Sabri Sidekli (International Journal of Evaluation and Research in Education (IJERE), 2018)
This study aims to investigate reading comprehension skills of the 4th graders in terms of the sentiments given in the reading text and to reveal that whether there is a meaningful difference for reading comprehension skills of different student groups or not.The sampling of the study has been selected randomly and it has been limited in primary schools in Muğla, Turkey. The sampling has been covered totally 387 4th graders, 209 of them have been female and 178 of them have been male students. The data collection instruments in the study have been determined as a personal information form and an achievement test on reading comprehension skills in terms of sentiments given in the reading texts. The answers of the students for the achievement test have been analyzed via percentage, frequency and arithmetic mean.According to the findings of the study; For the sentiments given in the reading texts, in line, the mostly understandable sentiments are happiness, fear and sadness. Additionally, there was a mean difference in terms of the level of reading comprehension skills. The students were mostly aware of texts containing happiness, and they understood sorrow in texts at least.